Mucosal adenovirus vaccine boosting elicits IgA and durably prevents XBB.1.16 infection in nonhuman primates - Gagne, Matthew; Flynn, Barbara J.; Andrew, Shayne F.; Marquez, Josue; Flebbe, Dillon R.; Mychalowych, Anna; Lamb, Evan; Davis-Gardner, Meredith E.; Burnett, Matthew R.; Serebryannyy, Leonid A.; Lin, Bob C.; Ziff, Zohar E.; et al. (Nature immunology, 2024)
A mucosal route of vaccination could prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replication at the site of infection and limit transmission. We compared protection against heterologous XBB.1.16 challenge in nonhuman primates (NHPs) ~5 months following intramuscular boosting with bivalent mRNA encoding WA1 and BA.5 spike proteins or mucosal boosting with a WA1–BA.5 bivalent chimpanzee adenoviral-vectored vaccine delivered by intranasal or aerosol device. NHPs boosted by either mucosal route had minimal virus replication in the nose and lungs, respectively. By contrast, protection by intramuscular mRNA was limited to the lower airways. The mucosally delivered vaccine elicited durable airway IgG and IgA responses and, unlike the intramuscular mRNA vaccine, induced spike-specific B cells in the lungs. IgG, IgA and T cell responses correlated with protection in the lungs, whereas mucosal IgA alone correlated with upper airway protection. This study highlights differential mucosal and serum correlates of protection and how mucosal vaccines can durably prevent infection against SARS-CoV-2. Seder and colleagues show that mucosal adenoviral-vectored vaccine boosting durably prevents infection in nonhuman primates of the highly transmissible, heterologous XBB.1.16 strain of SARS-CoV-2.